The impacts of emissions trading on world economies: Contemplation of baseline emissions paths and a ceiling on emissions trading - Claudia Kemfert (Fondazione Eni Enrico Mattei (FEEM), 2000)
This paper illustrates different scenarios of implementing an emissions trading scheme and investigates the economic implications of diverse baseline development paths and an additional limitation or ceiling on emissions trading. The analysis focuses on the impacts of dissimilar emissions reductions options, i.e. to decrease emissions by domestic action or by Annex B emissions trading. World economic impacts are investigated by a world general equilibrium model including 11 international regions and 4 production sectors. Various strategies including flexible instruments, like a ceiling on regional emissions trading and the interregional and intertemporal trade of emissions permits are simulated, compared and evaluated. It turns out that meeting the Kyoto target induces welfare losses to developed and developing countries, an emissions trading option can reduce global and regional welfare losses significantly. Essentially, these welfare losses depend considerably on assumed emissions baseline paths. A ceiling on emissions trading scheme diminishes positive economic effects on global and regional welfare, especially within economies in transition.
Keywords: Q4; E1; F0; 330; Emissions trading; energy economic modelling; baseline definition; Luftreinhaltung; Emissionshandel; Lizenz; Allgemeines Gleichgewicht; Wirkungsanalyse; Welt